Catalytic conversion of palm oil to gasoline over H-ZSM-5: effect of temperature and hydrotreatment of catalysts - Siregar, Tirena Bahnur; Saidina Amin, Nor Aishah; Abdul Karim, Siti Kartina (2005)

(untitled)
Catalytic conversion of palm oil to gasoline was performed over H-ZSM-5 zeolite catalyst. Palm oil was converted in a down flow fixed bed reactor at atmospheric pressure and weight hourly space velocity (WHSV) of 2.5 h-1. Temperature was varied in the range of 450-525°C and hydrogen flow rate for activation of 1-2 L/h. Increasing reaction temperature to 500°C increased the conversion of palm oil. OLP yield and gasoline selectivity increased with temperature until 500°C before decreasing slightly. Hydrotreatment of catalysts increased OLP and gasoline formation while coke and gas decreased. However, increasing the hydrotreating flow rate more than 1L/h gave little effect towards palm oil cracking activity.